The Legalization of Operational Permit in Continuing Ash-Shididiqiyyah Care Institution on Neglected Children Social Welfare Service - Siti Aminatun; Chulaifah Chulaifah (Balai Besar Penelitian dan Pengembangan Pelayanan Kesejahteraan Sosial, Kementerian Sosial, 2015)
The research is to dicusses the operational permit legalization of Ash-Shiddiqiyyah Care Institution to describe the operational permit legalization as responsibility in giving social service to neglected children. The informants in this research are chosen purposively, namely the managements of social welfare institution Ash-Shiddiqiyyah who give service to neglected children, apparatus of Social Agency of Yogyakarta Special Territory, apparatus of Investation and Joint Venture Board, and permanent and non-permanent donateurs. Data are gathered through indepth interview, observation, and documentary analysis. Data are analyzed through quantitative-descriptive technique to describe the process of operational permit legalization of the institutional care. The result shows that Ash-Shiddiqiyyah care institution as social welfare institution in handling the activities have got operational permit from legal institution. The operational permit indicates that the existence of institutional care is legal. It means that all things related to operational activities can be accounted publicily so that it gets accreditation by donateurs to participate. It is recommended to the local government, Investment and Joint Venture Board of Yogyakarta Special Territory and social welfare institution to keep overseeing and supervising so that the institution always gives service to people with social problem accountably and responsibly.